A beginner's guide to building better worlds : ideas and inspiration from the Zapatistas - Gahman, Levi (Policy Press, 2022)
This ambitious book offers radical alternatives to conventional ways of thinking about the planet's most pressing challenges, ranging from alienation and exploitation to state violence and environmental injustice. Bridging real-world examples of resistance and mutual aid in Zapatista territory with big-picture concepts like critical consciousness, social reproduction and decolonisation, the authors encourage readers to view themselves as co-creators of the societies they are a part of - and 'be Zapatistas wherever they are'. Written by a diverse team of first-generation authors, this book offers an emancipatory set of anti-colonial ideas related to both refusing liberal bystanding and collectively constructing better worlds and realities.